PENGARUH FRAUD HEXAGON TERHADAP KECURANGAN DALAM PELAPORAN KEUANGAN (Studi Empiris pada Perusahaan Propery dan Real Estate yang terdaftar di BEI periode 2021-2023) - Ananditya, Intan Azzahra Fajrina; Puspa Arum , Enggar Diah; Hernando, Riski (Jurnal Akuntansi Kompetif, 2025)
This study aims to examine the effect of the Fraud Hexagon elements on fraudulent financial reporting in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The Fraud Hexagon is represented by six independent variables: Financial Target, Working Experience, Related Party Transaction, Nature of Industry, Change of Auditor, and Frequent Number of CEO’s Picture. Meanwhile, fraudulent financial reporting as the dependent variable is measured using the F-Score model. A quantitative approach was employed in this research, utilizing a total sampling method and multiple linear regression analysis processed through IBM SPSS 26. The findings reveal that collectively, the Fraud Hexagon variables have a significant impact on fraudulent financial reporting. However, when tested individually, only the Nature of Industry variable shows a statistically significant effect, while Financial Target, Working Experience, Related Party Transaction, Change of Auditor, and Frequent Number of CEO’s Picture do not exhibit a significant influence on fraudulent financial reporting. Keywords: Fraud Hexagon, Fraudulent Financial Reporting, F-Score.